Icariin and related metabolites in fibrosis management: pharmacological properties and molecular mechanism - Zhao, Jiarui; Zhang, Wei (Frontiers in Pharmacology, 2025)
Fibrosis is a pathological hallmark of various chronic diseases and contributes significantly to organ dysfunction and poor clinical outcomes. Despite the availability of antifibrotic agents, their limited efficacy and adverse side effect profiles underscore the urgent need for safer and more effective therapeutic alternatives. Traditional Chinese medicines have emerged as promising candidates for fibrosis management. Epimedium, widely used in traditional Chinese medicine, exhibits notable antifibrotic activity, primarily attributed to its bioactive flavonoid icariin (ICA). However, the clinical application of ICA is hindered by its low bioavailability. Recent advances in extraction methods and drug delivery systems have improved the pharmacokinetic properties of ICA and related active metabolites, including icaritin and icariside II. These metabolites exert antifibrotic effects through multifaceted mechanisms, including anti-inflammatory and antioxidant activities, mitochondrial function modulation, apoptosis regulation, and autophagy. This review summarizes current insights into the molecular pathways through which ICA and related metabolites attenuate fibrosis, thereby supporting their potential for clinical translation in antifibrotic therapy.